Mediatization Strategies and Audience Responses in Constructing Narratives of Tolerance: A Netnographic Study of the Jakatarub Interfaith Community on Instagram - Wafa Salsabila Sakinah; Wawan Hernawan; Busro Busro (UIN Sunan Gunung Djati Bandung, 2024)
Purpose: This study aims to analyze how the interfaith community Jakatarub (Jaringan Kerja Antarumat Beragama) constructs a narrative of religious tolerance through mediatization strategies on the Instagram platform, as well as how audiences respond to these narratives. This research is significant given the shift of interfaith dialogue traditions from physical spaces to digital spaces, which opens new opportunities while also presenting challenges for strengthening social cohesion in Indonesia. Methodology: Using a qualitative approach with the netnography method, this study focuses on the Instagram account @jakatarub_bdg by examining 128 Feed and Reels posts published between January and December 2024, along with audience comments analyzed using Kozinets’ Cyber Media Analysis (CMA) framework. Findings: The findings reveal that the constructed tolerance narrative encompasses three main themes: interfaith dialogue (41%), social harmony (38%), and religious tolerance (21%). The mediatization strategies applied include media as conduits, media as language, and media as environment, which synergistically expand the reach of messages and create participatory spaces for audiences. Audience responses were predominantly positive and reflective, although some critical feedback sparked deeper discussions on the realities of tolerance at the local level. Research Implications: The implications of this study affirm the potential of social media as an effective medium for promoting interfaith dialogue, while highlighting the need for content moderation policies and adaptive communication strategies to anticipate risks of polarization and the reproduction of stereotypes. Originality/Value: The originality of this research lies in its integration of Hjarvard’s and Meyrowitz’s mediatization theory with a netnographic approach to a grassroots interfaith community in Indonesia—a focus that has been rarely explored in previous studies.